Lung transplantation in HIV-positive patients: a European retrospective cohort study. Issue 1 (14th July 2022) - Rouzaud, Claire; Berastegui, Cristina; Picard, Clément; Vos, Robin; Savale, Laurent; Demant, Xavier; Bertani, Alessandro; Verschuuren, Erik; Jaksch, Peter; Reed, Anna; Morlacchi, Letizia Corinna; Reynaud-Gaubert, Martine; et al.
Steady progress in antiretroviral therapy, with the introduction of new medications and the earlier institution of more aggressive treatment regimens, has markedly improved the outcomes of HIV infection [1]. The longer life expectancy provided by optimal management is associated with an increased risk of eventually developing chronic medical conditions, including lung diseases and pulmonary arterial hypertension (PAH), many of which can be treated but not cured [2, 3]. In selected HIV-positive patients, lung transplantation provided good transplant and patient survivals, without more infections than reported in HIV-negative patients. Further work is needed to determine the best immunosuppressive regimens. https://bit.ly/3kyLnDL